Export of agricultural products produced in the Uzbekistan SSR and its characteristics - Nasriddinovich, Choriyev Fazliddin (Goodwood Publishing, 2025)
Purpose: This study aims to analyze the historical role of the Uzbek Soviet Socialist Republic (Uzbek SSR) as the main producer and exporter of agricultural products, especially cotton, fruits, vegetables, and processed goods, while emphasizing how all exports were controlled by the Soviet Union’s central planning system. Research methodology: The research applies a historical-analytical approach using methods of analysis and synthesis, retrospective and comparative analysis, as well as generalization and dialectical methods. Archival documents, official records, and secondary sources were examined to trace the dynamics of agricultural exports and their specific features. Results: The findings indicate that the Uzbek SSR became the “cotton heart” of the USSR, producing more than 60% of its cotton. Agricultural exports, including fruits, vegetables, and oils, were not only economic assets but also instruments of Soviet foreign policy and soft power. These exports were presented in international exhibitions and used in foreign aid packages to strengthen ties with countries in Africa, Asia, and Europe. However, reliance on monoculture and centrally imposed quotas contributed to environmental degradation and food insecurity. Conclusions: Centralized planning facilitated Uzbekistan’s transformation into a strategic agricultural hub but also created systemic inefficiencies and long-term vulnerabilities, particularly in ecological and economic sustainability. Limitations: The study is limited to the availability of Soviet and post-Soviet archival materials, which may not fully capture local perspectives or informal trade practices. Contribution: Contributes to Soviet and Central Asian studies by analyzing central planning’s impact on Uzbekistan’s agricultural exports.